China-Central Asia Relations: A Socio-Economic and Security Analysis of Bilateral Ties - Iram Khalid; Rehana Saeed Hashmi; Zainab Ahmed (Journal of Political Studies, 2016)
China is a global power and economic giant in search of diversified resources to run its industry and potential markets which it can tap to remain a leading seller. The next door neighbor, Central Asia, provides with this opportunity. Central Asian energy resources are a stimulus for all global powers. United States interest in the region alarms China and makes it more cautious of its interests. China is investing hugely in Central Asian energy infrastructure to being energy hungry. It eyes on Central Asian oil and gas resources. After disintegration of Soviet Union, Central Asia could not step out of isolation and economic backwardness. Here interests of China and Central Asia converge. However, the cultural and religious divergence may become a hindrance in smooth transition to bilateral engagement. This paper endeavors to analyze the enormity of economic and security benefits of this relation which may overcome the social gaps.